Internal conflict and regional security in South Asia : approaches, perspectives and policies - Dahal, Shiva Hari (UNIDIR, 2003)
The aim of this paper is to provide a more effective framework for the analysis and management of internal conflict and security, using South Asia as a case study. The paper is divided into four sections. Section 1 provides an introduction to the region. Section 2 reports on the current status of internal conflicts in the region (Bhutan, Bangladesh, India, Maldives, Nepal, Pakistan, Sri Lanka). Section 3 outlines a conceptual framework for the analysis of conflict, while section 4 discusses how this framework can be used for the purpose of conflict management.--Publisher's description.